Fully distributed versus semi-distributed process simulation of a highly managed watershed with mixed land use and irrigation return flow. (June 2021) - Veettil, Anoop Valiya; Green, Timothy R.; Kipka, Holm; Arabi, Mazdak; Lighthart, Nathan; Mankin, Kyle; Clary, Jane
Abstract: Spatially distributed process models represent soil-water-plant-nutrient interactions within a watershed. We investigated spatial patterns of water balance components and nitrate transport simulated using the fully distributed AgES (Agricultural Ecosystems Services) and the semi-distributed SWAT (Soil and Water Assessment Tool, 2012) models in the Big Dry Creek Watershed, a mixed agricultural and suburban watershed in semi-arid Colorado, USA. We analyzed patterns of hydrological fluxes using daily model outputs for the period 2010–2018. The two models simulated drastically different spatial patterns. SWAT predicted extremely low interflow and routed excess irrigation water to surface runoff and groundwater discharge. AgES produced realistic estimation of streamflow, irrigation return flows, and nitrate; simulation of less surface runoff and greater interflow and baseflow contributed to improved simulation of nitrate transport in the interior watersheds. This study demonstrated the impacts of simulating spatially explicit hydrology that captures interactions among fields and other areas within a managed watershed. Highlights: The fully distributed AgES model and semi-distributed SWAT model simulated hydrology of an intensively managed semi-arid watershed. Overall, AgES simulated daily streamflow and nitrate concentrations better than SWAT. AgES and SWAT simulated drastically different spatial patterns of water routing within the watershed. Accurate treated wastewater inputs and simulated irrigation return flow were critical for simulating nitrate transport.